St. Joseph's, Cloud County - Jones, Kathyrn (Kansas State University, The Chapman Center for Rural Studies, 2011)
It is a sunny Saturday afternoon in Cloud County, Kansas, when the peace of the rolling tallgrass prairie is broken by cries of “Au feu! Au feu!” The French Presbyterian Church just south of St. Joseph’s was ablaze under mysterious circumstances.
Kathryn Jones, “St. Joseph's, Cloud County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/31.
Keywords: Cloud; Concordia; French Canadian; Miltonvale; French Presbyterian; Quebecoise